Vernacular Domestic Architecture Through Samples at Ayvacik Kiran Section - Kocabicak, Evren; Kara Pilehvarian, Nuran (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
In studies on traditional or vernacular houses, the tradition of generalization has been replaced by subjective studies where each example is analyzed in its own context during the last quarter of the century. Within this framework, the purpose of the present article is to analyze the vernacular architecture in Ayvacik Kiran Section villages through samples and to investigate the origins of the current house typology. For this purpose, first, the parameters that may affect the architectural pattern in the region were analyzed; then, two houses representative of the architectural culture in the region were selected among 50 samples studied between 2014 and 2016, and architectural characteristics of these houses were determined. In conclusion, origins of this house type were determined.
Keywords: Ayvacik; vernacular house; Kiran section; megaron; stone masonry structure; Architecture